KAPASITAS INFRASTRUKTUR ANGKUTAN KERETA API LOGISTIK - Muhammad Rifni; Oce Prasetya (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2016)
Very limited capacity of the highway in some economies tract, such as the Trans Java traffic, has an impact on increasing the travel time especially in the use of rail transport, so that a certain pathway requires capacity building and the development of new lines gradually. The purpose of this research was to determine the capacity of rail transport infrastructure that is optimal for the distribution of goods, especially as the company managed by PT. Railway Logistics or KALOG. Another problem is how the government's role and the flow of freight transport demand. In the discussion, through a variety of existing data, the authors use research with phenomenological approach on the basis of qualitative analysis methods interpretative paradigm. Results are expected to be useful for improving knowledge about the needs of rail freight transport on goods distribution on the Java Island. The results of this research will be published in scientific journals.